(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The application of computational simulations based on topology achieves an optimization of the non-parametric topology of the bodies or parts, such as weight reduction or deformations. OT is a numerical method that has captured the interest of engineers and scientists in recent years, as it allows the synthesis of structures or bodies with optimal values of one or more of their physical parameters. The problem of maximum stiffness with volume restriction is also raised, which basically consists of finding the material distribution in a domain where the maximum stiffness remains constant for a given original load, restricting the final volume of the material used in the structure or part. . This paper presents an implementation of the OT technique applied to the design of a Savonius type vertical axis wind generator casing to define the geometric shape in a scenario of static loads that vary their direction during the iterations of the calculation; with the aim of obtaining an optimal CAD geometry, evaluating the behavior of the OT in thin parts.